Pengaruh Inventory Turnover, Tangible Asset dan Capital Structure Terhadap Pertumbuhan Laba. (Studi pada Perusahaan Pertambangan Batubara yang Terdapat pada BEI Tahun 2015-2019) - Hizkia Andrew Kusuma, - (2020)
This research aims to determine the effect of Inventory Turnover, Tangible Assets and Capital Structure on Profit Growth. The object research is coal mining companies listed on the Indonesia Stock Exchange, the period 2015-2018. The research method used is descriptive method with a quantitative approach. The research sample was selected using purposive sampling method. The total sample of the study was 10 companies in the consumer goods industry sector. The data used is secondary data obtained from annual reports and financial reports found at www.idx .co.id and the websites of each manufacturing company in the consumer goods industry sector. Data analysis was performed using multiple regression models with the help of SPSS version 20.0 software. From the results of tests that have been done, partially regression test (t test) shows that the independent variable Capital Structure has a significant effect on profit growth. Meanwhile, the independent variables of nentory Turnover and Tangible Assets tidal: have a significant effect on profit growth. Keyword: Growth Profit, Invetory Turnover, Tangible Assets, Capital Structure